Ectopic Breast Tissue in the Inguinal Region: A Case Report and Suggestion of Indications for Excision - Choi, Jangyoun; Yang, Young Bin; Oh, Deuk Young (Frontiers in Surgery, 2022)
We report a rare case of ectopic breast tissue situated in a unique location. A 50-year-old female patient came to our institution complaining of a bulge in the inguinal area. CT was unremarkable other than a benign-looking conglomeration of lymph nodes around the inguinal canal. However, excisional biopsy proved otherwise, with strong expression of breast-related immunohistochemical markers on pathology. Based on histological findings, the diagnosis of ectopic breast tissue was made. Since the vast majority of ectopic breast tissue is found around the breast mound, axilla, and along the milk line, this case is peculiar in its location. This report shares our experience and provides indications for excision of incidental ectopic breast tissue.